Structure refinement and up-conversion of Ho3 +/Er3 + Co-doped 12CaO·7Al2O3. (15th October 2016) - Liao, Song-Yi; Yao, Rui; Chen, Xiao-Yu; Wang, Guang-Rong; Zheng, Feng
Abstract: Crystal structures, thermodynamics characters and optical properties of pure 12CaO·7Al2 O3 (C12A7) and Ho 3 + /Er 3 + co-doped C12A7 (C12A7-Ho 3 + /Er 3 + ) derivatives have been studied using XRD, DSC/TG and Raman spectra analysis, respectively. Testing samples were sintered at 1173 K from compacted precursor powders after co-precipitation. Effect of pH change on grain size of C12A7 was estimated via Scherrer's Equation. Activation energy of crystal growth for C12A7 polycrystals was measured according to Kissinger/Ozawa methods to be 238/258 kJ·mol − 1 respectively. Lattice constant ( a ) and Reference Intensity Ratio ( RIR ) of pure C12A7 were evaluated to be a = 12.0122(2) Å and RIR = 0.79 (5%). Fluorescence effects of Raman spectra around 1200–1400 and 2000–2500 cm − 1 and pure visible up-conversion emission of 520–540 nm were observed from C12A7-Ho 3 + /Er 3 + powders under 488 nm laser diode and 793 nm Xe lamp excitation, respectively. Three relaxations and cooperative transformation mechanisms of Ho 3 + /Er 3 + ions were proposed to explain up-conversion of pure green light process. Graphical abstract: Highlights: RIR value of 0.79 with a = 12.0222(2) Å were determined for pure C12A7. Activation energy of growth was calculated by Ozawa/Kissinger methods. A through study was conducted for thermal characters of C12A7 precursor powders. Er 3 + is primary activator and sensitizer for Ho 3 + in C12A7-Ho 3 + /Er 3 + . Three cooperative relaxations between Er 3 + and Ho 3 + were proposed for up-conversion.